Marketing integration in cross-border mergers and acquisitions: conceptual framework and research propositions - Sinkovics, Rudolf R. (Inderscience Enterprises Ltd., 2014)
As for Mergers and Acquisitions (M&As), cross-border M&As are particularly problematic and complex.The most challenging issue is the integration of different management styles and departmental practices.Once the integration seeps deeper into functional levels, the M&A commitment offered at strategic level is faced with operational implementation challenges.The marketing departmental function is usually heavily involved in this integration process.Research on marketing integration in relation to M&As has paid little attention to the process of combining resources from two similar departments, particularly in a cross-border M&A context. Furthermore, existing research does not clearly highlight those factors that contribute to successful marketing integration.Hence, this paper discusses the phenomenon of marketing integration in the cross-border M&A context. Collaboration, interaction, marketing synergy and redeployment of marketing resources are proposed as antecedents to the integration.Drawing from the extant literature, propositions are developed and mechanisms to improve M&A integration performance are elaborated.